Online scientific research on placentophagy: a bibliometric analysis - Paloma Elisama de Oliveira Morais; Melissa Santos Nassif; Andreia Cristina Barbosa Costa; Patrícia Scotini Freitas; Rômulo Severo Sampaio; Isabelle Cristinne Pinto Costa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To classify the bibliometric indicators of online scientific research on placentophagy. Methods: A bibliometric study was conducted to quantify the scientific production of authors and institutions with the aim of highlighting the growth and impact of these publications nationally and internationally. The Bradford Law, network maps, and textual statistics were used, with searches conducted in libraries and databases in October 2021. Results: The sample consisted of 64 articles, whose primary authors were associated with 49 institutions, and mostly with degrees in anthropology. The United States of America was the country that published the most papers on the theme, and most studies were reviews with individual production. Through the term analysis, it was found that the predominant themes regarding placentophagy were the following: Alternative therapy for women's health, methodologies used for research in this area, period of placenta ingestion (postpartum period), and its benefits. Conclusion: The bibliometric indicators found are essential for the development of future research.